2010
DOI: 10.1038/oby.2009.410
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers' Knowledge, Practices, and Perceived Barriers to the Treatment and Prevention of Childhood Obesity

Abstract: This study evaluated primary care providers' (PCPs, pediatricians, and nurse practitioners) knowledge, current practices, and perceived barriers to childhood obesity prevention and treatment, with an emphasis on first-year wellchild care visits. A questionnaire was distributed to 192 PCPs in the primary care network at The Children's Hospital of Philadelphia (CHOP) addressing (i) knowledge of obesity and American Academy of Pediatrics (AAP) guidelines, (ii) anticipatory guidance practices at well visits regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
93
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 27 publications
4
93
0
2
Order By: Relevance
“…Literature shows that general practitioners (GPs) acknowledge their potential role in the management of childhood obesity, but the majority of GPs do not address weight in regular consultations 6. Barriers include the limited evidence base for effective management7 and perceptions held by primary care providers that parents and children lack the motivation to change 8. Notwithstanding these issues, with young people attending primary care at least annually there are many opportunities for detection of weight issues and preventive health advice 9…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that general practitioners (GPs) acknowledge their potential role in the management of childhood obesity, but the majority of GPs do not address weight in regular consultations 6. Barriers include the limited evidence base for effective management7 and perceptions held by primary care providers that parents and children lack the motivation to change 8. Notwithstanding these issues, with young people attending primary care at least annually there are many opportunities for detection of weight issues and preventive health advice 9…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Competing priorities in a busy clinical practice in addition to perceived barriers, such as lack of time, practice, and community level resources, and reimbursement may make it less likely for providers to spend time discussing obesity. 5,18,19 Previous studies have explored practice characteristics (number of staff, location, and access to educational material and community resources) and preventive service delivery, not including obesity. 20,21 Practice characteristics vary greatly, but these characteristics may impact the provider's ability to provide preventive services, such as obesity-related counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Another report of 87 primary care pediatricians and nurse practitioners found that only 26% knew the definition of childhood obesity and 9% knew its prevalence, whereas only 39% and 44% knew the American Academy of Pediatrics' guidelines for exercise and juice consumption, respectively. 10 More than 35% of the respondents never discussed fast food, television, or candy and 55% never discussed exercise at well child visits in the first year of life. The management of obesity in primary care settings is an emerging area of healthcare research, [11][12][13] and greater information dissemination on core behavior change strategies by health professionals is needed.…”
mentioning
confidence: 99%